Stability of morphine, morphine-3-glucuronide, and morphine-6-glucuronide in fresh blood and plasma and postmortem blood samples - Skopp, Gisela; Pötsch-Schneider, Lucia Edeltraud; Klingmann, Andrea; Mattern, Rainer (Journal of analytical toxicology, 2001)
The present study was designed to determine the stability of morphine and its glucuronides in spiked fresh blood and plasma from live individuals as well as in four authentic postmortem blood specimens for a time interval of up to six months. The samples were stored in glass vials at −20°C, 4°C, and 20°C. Additionally, spiked samples were exposed to light through window glass and subjected to a forced-degradation study at 40°C. Data were established using solid-phase extraction and high-performance liquid chromatography coupled to atmospheric pressure ionization mass spectrometry for isolation and quantitation, providing a sensitive and specific detection method for the parent drug in the presence of its glucuronide metabolites. Morphine and its glucuronide metabolites were found to be stable in both blood and plasma at 4°C for the whole observation period. In postmortem blood the analytes were stable only when stored at −20°C. The thermal decomposition of morphine and morphine-6-glucuronide in spiked blood and plasma could be interpretated using pseudo first-order kinetics. Photodegradation of morphine-3-glucuronide in plasma was consistent with a second-order reaction. In postmortem samples the degradation pattern differed completely from that observed in fresh blood and plasma. The elevated morphine levels observed were primarily due to postmortem hydrolysis of morphine glucuronides.
Gesehen am 28.04.2021